Analytical Approach to Value Options with State Variables of a Lévy System - Nguyen-Thanh, Long (Review of Finance, 2003)
Abstract In this paper we present an analytical method in pricing European contingent assets, whose state variables follow a multi-dimensional Lévy process. We give an explicit formula for the hypothetical European “two-price” call option price by means of the conditiona characteristic transform. The work not only unifies and extends the option pricing literature, which focuses on the use of the characteristic function, but also provides the way to formalizeand unify the valuation of the option price, the valuation of the discount bond price, the valuation of the scaled-forward price, and the valuation of the pricing measure in incomplete markets. JEL Classification codes: G13